KOORDINASI TIM PENATAAN KEGIATAN PENGELOLAAN DAN PENGUSAHAAN SARANG BURUNG WALET DI KOTA SINGKAWANG - R i k k y E.42009087 (FISIP Universitas Tanjungpura Pontianak, 2022)
This script intend to determine the coordination of Activity Management and Operational Team for Swallow birdnest at Singkawang City undertake enforcement of the permition of the company that does not have a license. This title taken based by the issues of swallow birdnest’s permition that can not published yet from activity management and operational team for swallow birdness at Singkawang City because the lack of coordination. This research uses qualitative analysis with the three stages of data analysis that is data reduction, data display and conclusion. There search site is at the Civil Service Police Unit; Investment Office and Integrated Services; Department of City Planning, Lands and Human Settlements; Department of Agriculture and Forestry; Environment Agency within Government environments Singkawang. Subjects were each agency’s head where the study was conducted. The results reveal yet goes coordination within the activity management and operational team for swallow birdness at Singkawang City caused by leaders who can not perform their duties as coordinator and the unsustainable implementation of the coordination as assessed using the elements of coordination by JamesbD.Mooney. Keywords: Coordination, Control, Swallow Birdnest’s License.